An Experimental Animal Model of Photodynamic Optic Nerve Head Injury (PONHI) - Mantopoulos, Dimosthenis (Curr Eye Res, 2016)
PURPOSE: Anterior ischemic optic neuropathy (AION) is the most common cause of non-glaucomatous optic nerve head (ONH) injury among older adults. AION results from a sudden ischemic insult to the proximal portion of the optic nerve, typically leading to visual impairment. Here, we present an experimental model of photodynamically induced ONH injury that can be used to study neuroprotective modalities. METHODS: Intraperitoneal injection of mesoporphyrin IX was followed by photodynamic treatment of the ONH in one eye of Brown-Norway rats; the fellow eye received the reverse sequence as a sham control. Fluorescein angiography (FA), spectral domain optical coherence tomography (SD-OCT), and visual evoked potential (VEP) recordings were performed at different time points following laser treatment. Immunohistochemistry was used to monitor apoptotic cell death (TUNEL) and macrophage infiltration (CD68). Cytokine levels were evaluated using enzyme-linked immunosorbent assay (ELISA). RESULTS: FA showed early hyperfluorescence and late leakage of the ONH, while SD-OCT revealed optic nerve edema. No leakage or other abnormalities were detected in control eyes. VEPs were significantly reduced in amplitude and showed prolonged responses compared to sham eyes. The number of apoptotic retinal ganglion cells was elevated one day after laser treatment (13.77 ± 4.49, p < 0.01) and peaked on day 7 (57.22 ± 11.34, p < 0.01). ONH macrophage infiltration also peaked on day 7 (101.8 ± 9.8, p < 0.05). ELISAs performed showed upregulation of macrophage chemoattractant protein-1 and macrophage inflammatory protein-2 on days 3 and 1, respectively. CONCLUSIONS: Photodynamic treatment of the ONH after administration of mesoporphyrin IX leads to macroscopic, histologic, and physiologic evidence of ONH injury. Given the long half-life of mesoporphyrin IX and the ease of intraperitoneal injections, this new model of photodynamically induced ONH injury may be a useful tool for studying optic nerve injury and possible neuroprotective treatments.